2000
DOI: 10.1159/000010264
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcome after Surgical Treatment of Ectopic Pregnancy

Abstract: Objectives: Reproductive outcome after laparoscopy or laparotomy performed for treatment of ectopic pregnancy. Methods: Data of 104 women were collected by a questionnaire and from medical records. Results: No differences in pregnancy rate were found comparing the two different operative procedures. Women with a normal contralateral fallopian tube had a better pregnancy rate compared with those with a damaged contralateral tube. Conclusions: The crucial factor for future reproductive outcome after surgical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…During the surgical treatment of EP by both laparatomy and laparoscopy, the state of the contra-lateral tube is noted. The condition of the contra-lateral tube has been reported to play a crucial role in subsequent fertility of patients with EP [31,32]. Most of the patients in our report had ampullary ectopic pregnancy (83.3%) which is consistent with studies from other centers [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…During the surgical treatment of EP by both laparatomy and laparoscopy, the state of the contra-lateral tube is noted. The condition of the contra-lateral tube has been reported to play a crucial role in subsequent fertility of patients with EP [31,32]. Most of the patients in our report had ampullary ectopic pregnancy (83.3%) which is consistent with studies from other centers [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…Both these studies included women with their second or third ectopic pregnancy. Several studies have shown that fertility is reduced by one‐third for each additional ectopic pregnancy between the first and the third ectopic pregnancies 17,18 . Our study only included patients with their first ectopic pregnancies and had a longer follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Others perform survival analysis, but do not adjust for confounding factors 7,8,14 . Some do not report whether or not the women desired pregnancy, and fail to report how subsequent pregnancies were achieved 13,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of persistent ectopic pregnancy was 8% and all incidents followed conservative surgery. The risk of persistent trophoblast varies from study to study and both lower 8,10 , and higher 15,20 incidences are reported. It is very likely that the discrepancy depends on different definitions of persistent ectopic pregnancy, although factors such as patient selection and differences in operative skill could play a role.…”
Section: Discussionmentioning
confidence: 99%